INFLAMMATORY DISEASES OF THE FACIAL AREAS IN CHILDREN - Nasullayeva Shahribonu Hayot qizi (Journal of new century innovations, 2024)
Abstract: Since children's bodies are still young, the inflammatory process in the face-jaw area quickly escalates. This not only has a negative impact on the general condition of the child, but can also cause the child's death. For this reason, in this article, the inflammatory diseases that occur in the face-jaw system of children, how they affect the child's body, what complications they cause, and treatment measures are briefly covered. The reasons for such a rapid development of inflammatory diseases in children are explained in detail. In addition, the types and classifications of inflammatory diseases in the face-jaw area in children were specially discussed